Comprehensive performance analysis of a high-temperature PEM fuel cell under different operating and design conditions - Bayat, Mutlucan; Özalp, Mehmet; Gürbüz, Hüseyin (ELSEVIER, 2022)
The performance of a high-temperature PEM fuel cell (HT-PEMFC) is highly affected by various operational and design parameters. Therefore, this paper presents comprehensive energy, entropy, and exergy analysis of the HTPEMFC by developing a novel zero-dimensional and isothermal model. The preliminary results were compared with two experimental studies by applying statistical methods, including the root mean square error (RMSE) and R-squared (R2 ), to validate the proposed model. Accordingly, RMSE was determined as 0.046 and 0.028, whereas R2 was computed as 0.986 and 0.991 for operating temperatures of 423 K and 433 K, respectively. Besides, some significant parametric studies were conducted to determine how these parameters impact the performance of the HT-PEMFC. As a result, increasing the operating temperature contributes to an increase of 39.71% and 38.67% in energy and exergy efficiency, respectively, whereas raising the pressure provides only a 2.66% improvement in both efficiencies compared to the base case. Furthermore, boosting the humidity level contributes to an increase of 8.02% and 8.03%, whereas reducing the thickness improves the energy and exergy efficiency by 9.94% and 9.93%, respectively. Therefore, the temperature, membrane thickness, and relative humidity have a more noticeable impact on the fuel cell performance than the operating pressure.
Keywords: High-temperature; PEM fuel cell; HT-PEMFC; Energy; Entropy; Exergy analysis; Different operating conditions